2003
DOI: 10.1046/j.1365-2052.2003.01023.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and physical mapping of genes expressed in the corpus luteum in cattle1

Abstract: A representational difference analysis was performed to identify genes expressed in the corpus luteum of cattle. The corpus luteum is an ovarian structure that is essential for the establishment and maintenance of pregnancy. Knowledge of gene expression and function of corpus luteum will be important to improve fertility in humans and domestic animals. Housekeeping genes were removed from the corpus luteum representation (tester) using skeletal muscle as the subtracting agent (driver). A total of 80 clones of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Approximately 2 × 10 5 cDNA clones were transferred to nylon membranes by colony lifts (Sambrook et al. 1989) and screened with the previously identified BTCL9 RDA fragment (Bønsdorff et al. 2003).…”
Section: Screening Of a Cdna And A Bac Library With Btcl9mentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 2 × 10 5 cDNA clones were transferred to nylon membranes by colony lifts (Sambrook et al. 1989) and screened with the previously identified BTCL9 RDA fragment (Bønsdorff et al. 2003).…”
Section: Screening Of a Cdna And A Bac Library With Btcl9mentioning
confidence: 99%
“…2002), using the primers listed in Table 1. The mapping was performed and analysed as previously described (Bønsdorff et al. 2003).…”
Section: Rh Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has been used to accelerate gene discovery in a variety of bovine tissues including the ovary [14], mammary gland [15], embryo [16], foetus [17], and multiple tissues [18]. In addition, a recent study reported the identification and mapping of 11 gene sequences preferentially expressed in the bovine CL [19]. The generation of ESTs is vital to the growing area of bovine functional genomics and in facilitating large-scale gene expression studies [20,21], gene mapping, and the identification of genes influencing economically important traits [22,23].…”
Section: Introductionmentioning
confidence: 99%